Pemanfaatan Booklet Kreasi Menu Makanan Pendamping ASI (Mp-Asi) UNTUK Meningkatkan Motivasi Ibu Balita dalam Pencegahan Stunting - Windayanti, Hapsari; Widayati; Luvi Dian Afriyani; Wahyu Kristiningrum (INDONESIAN JOURNAL OF COMMUNITY EMPOWERMENT (IJCE), 2025)
Infants and toddlers are part of an important phase in the life cycle, marked by very rapid physical growth and social development. This period is marked by high nutritional needs to support the speed of children's growth and development. Lack of nutritional intake in the first 1,000 days of life, covering the period from in the womb to the age of two years. This can have a serious impact not only on physical growth, but also on the child's cognitive development, intelligence, and productivity in the future. As a result, the child's development as an adult is at risk of being suboptimal.In Indonesia, one in three toddlers experiences stunting, which means growth disorders due to chronic malnutrition. Data from Riskesdas (2018), shows that the prevalence of stunting reaches 30.8%. One of the areas facing this problem is the Bergas Health Center work area, where a number of toddlers were found to be stunted.. One effort that can be made to overcome stunting is through the provision of appropriate Complementary Foods (MP-ASI), according to the child's age and nutritional needs. MP-ASI that is presented in an attractive, varied, and balanced way can increase toddlers' interest in eating. Seeing this problem, the community service team took the initiative to provide education to mothers of toddlers about creating MPASI menus. This activity was carried out through a lecture method and assisted by an informative booklet that was designed attractively. Previously, this kind of booklet had never been provided in the Bergas Health Center area. This community service program includes three stages, namely the preparation, implementation, and evaluation stages. The activity has been carried out three times in toddler classes located in Jatijajar, Randugunting, and Bergas Lor, with a total of 26 mothers/caregivers participating.  The results of the implementation showed an increase in motivation from mothers/caregivers in preventing stunting through providing appropriate MPASI.   ABSTRAK Bayi dan balita bagian dari fase penting dalam siklus kehidupan, ditandai pertumbuhan fisik serta perkembangan sosial yang sangat cepat. Periode ini ditandai dengan kebutuhan gizi yang tinggi untuk mendukung kecepatan tumbuh kembang anak. Kekurangan asupan gizi pada 1.000 hari pertama kehidupan, mencakup masa sejak dalam kandungan hingga anak berusia dua tahun. Hal ini dapat berdampak serius, tidak hanya pada pertumbuhan fisik, tetapi juga pada perkembangan kognitif, kecerdasan, dan produktivitas anak dimasa mendatang. Akibatnya, perkembangan anak saat dewasa berisiko menjadi tidak optimal. Di Indonesia, satu dari tiga balita mengalami stunting, yang berarti gangguan pertumbuhan akibat kekurangan gizi kronis. Data dari Riskesdas (2018), menunjukkan bahwa prevalensi stunting mencapai angka 30,8%. Salah satu daerah yang menghadapi permasalahan ini adalah wilayah kerja Puskesmas Bergas, ditemukan sejumlah balita yang mengalami stunting. Salah satu upaya yang dapat dilakukan untuk mengatasi stunting adalah melalui pemberian Makanan Pendamping ASI (MP-ASI) yang tepat, sesuai dengan usia dan kebutuhan gizi anak. MP-ASI yang disajikan secara menarik, bervariasi, dan bergizi seimbang dapat meningkatkan minat makan balita. Melihat permasalahan tersebut, tim pengabdian masyarakat berinisiatif memberikan edukasi kepada ibu balita mengenai kreasi menu MP-ASI. Kegiatan dilakukan melalui metode ceramah dan dibantu dengan booklet informatif yang dirancang menarik. Sebelumnya, booklet semacam ini belum pernah diberikan di wilayah Puskesmas Bergas. Program pengabdian masyarakat ini mencakup tiga tahapan, yakni tahap persiapan, pelaksanaan, dan evaluasi.  Kegiatan telah dilaksanakan sebanyak tiga kali, di kelas balita yang berlokasi di Jatijajar, Randugunting, dan Bergas Lor, dengan peserta sebanyak 26 ibu/pengasuh.  Hasil pelaksanaan menunjukkan adanya peningkatan motivasi dari para ibu/pengasuh dalam mencegah stunting melalui pemberian MPASI yang tepat.